The Study on Early-Age Expansion and Shrinkage Model of Massive Self-Compacting Concrete Pumped in Steel Tube Column - Zhen-jun He; Meng-jia Ding; Zhen-wei Wang; Xue-sheng Zhang; Mei-gen Cao; Ming-wei Lei (Advances in Civil Engineering)
Massive self-compacting concrete pumped in steel tube columns has been used more and more widely in super high-rise buildings and bridge engineering at present. The early-age expansion and shrinkage performance of its core mass concrete is an important index to ensure the stress state of triaxial compression and structural safety. However, no relevant reports have been found. In view of the actual building with the height of 265.15 meters, the early-age expansion and shrinkage tests of the massive self-compacting concrete pumped in full-scale columns with the height of 12.54 m and 12.24 m and diameter of 1.3 m and 1.6 m were carried out by means of strain gauges embedded in concrete-filled steel tubes (CFSTs). The early-age variation regularity of the vertical and horizontal expansion and shrinkage strains for the core concrete with the diameter of steel tube, development time, temperature, the pouring pressure, expansion stress, and so on is given. The calculation model of its early-age deformation strains is presented in this paper, which is in good agreement with the experimental results. It provides the basis of experimental and theoretical analyses for shrinkage compensation of massive self-compacting concrete pumped in steel tube columns.